Oral Supplementation with Herbal Phytohormones on the Reproductive Performance of Female Climbing Perch (Anabas testudineus) - Helmizuryani Helmizuryani; Muhammad Nizar; Muhammad Akbar (Journal of Global Sustainable Agriculture, 2026)
Limited seed due to low reproductive performance of the parent is still an obstacle in the cultivation of betok fish (Anabas testudineus). The use of natural phytohormones based on herbal ingredients has the potential to be a safe and environmentally friendly alternative to increase fish reproduction. This research aims to evaluate the effectiveness of various herbal ingredients on the reproductive performance of betok fish and determine the best herbal ingredients based on the gonad maturity level (TKG) and gonad maturity index (IKG). The research was carried out in the aquaculture wet laboratory, Faculty of Agriculture, Muhammadiyah University, Palembang for 45 days with 4 treatments and 3 repetitions, P1: Treatment with turmeric extract, P2: Treatment with katuk leaf extract, P3: Treatment with papaya leaf extract and P4: Treatment with sprout/bean sprout extract. The research results showed that natural phytohormone supplementation based on herbal ingredients provided a positive response to the reproductive performance of betok fish (Anabas testudineus). Sprout/bean sprout extract is the best treatment in increasing growth, gonad maturity level, and gonad maturity index, while papaya leaf extract produces the highest fecundity. All treatments resulted in a 100% survival rate and did not reduce the water quality of the rearing media. Thus, herbal ingredients have the potential to be used as a natural alternative to increase the reproduction of betok fish in sustainable cultivation activities.